2021
DOI: 10.1002/ijch.202100081
|View full text |Cite
|
Sign up to set email alerts
|

How to Identify the Crystal Growth Unit

Abstract: The structure and composition of the crystal growth unit are of huge fundamental and practical consequence. We propose a method to identify the solute species that incorporates into the growth site on crystal surfaces, the kinks, which rests on the kinetics of the elementary reaction at the kinks. We use as model crystals olanzapine, an antipsychotic medication, and etioporphyrin I, a field-effect transistor. We combine time-resolved in situ atomic force microscopy with Raman and absorption spectroscopies, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…400 nm, and four Q bands in the wavelength range 475 to 630 nm ( Fig. 1 C ) attributed to distinct transitions of the conjugated π electron systems of the constituent pyrroles ( 44 46 ). The Soret and the Q bands are similarly structured in the three alcohols and DMSO ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…400 nm, and four Q bands in the wavelength range 475 to 630 nm ( Fig. 1 C ) attributed to distinct transitions of the conjugated π electron systems of the constituent pyrroles ( 44 46 ). The Soret and the Q bands are similarly structured in the three alcohols and DMSO ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Olanzapine (pictured in Figure ) is a benzodiazepine agent used for treatment of psychoses such as schizophrenia . Prior studies have investigated the crystal growth of olanzapine from solution and demonstrated that growth occurs by incorporation of dimers into the crystal surface. , The growth unit is thus considered to be a centrosymmetric olanzapine dimer. Previous research further describes how the dimer growth unit is constructed and treated within ADDICT .…”
Section: Resultsmentioning
confidence: 99%
“…Succinic acid is a centrosymmetric molecule, and it has been established that the growth unit in olanzapine is the centrosymmetric dimer (Figure ), , and so these cases can both be treated as centrosymmetric growth units. Figure shows the predicted morphologies of succinic acid grown from water and olanzapine grown from ethyl acetate.…”
Section: Crystal Growth and Morphology Predictionmentioning
confidence: 99%